The Influence of Product Quality, Price Perception, and Brand Image on Furniture Purchase At PT. Jati City Furindo Jepara - Hidayat, Ari; Triyani, Dian; Prapti, Lulus (Universitas Semarang, 2019)
There are some factors that can influence the success and failure of furniture companies include product quality, price perception, and brand image that can have an impact on consumer purchasing decisions. The aimed of study to analyze the influence of product quality, price perception, and brand image on purchasing decisions.The object of this study is PT Kota Jati Furindo Jeparam, this companies is one of the companies engaged in the furniture trade located on Jl. Jepara-Bangsri No.Km 6.5 hamlet 1, Suwawal, Mlonggo, Jepara, Central Java. The samples of this study are consumers who bought furniture at PT Kota Jati Furindo Jepara. The reasearcher use linear regression to analyze this study.The results showed that product quality, price perception and brand image had a positive and significant effect on purchasing decisions. Better product quality, price perception, and brand image of furniture will further enhance consumer purchasing decisions on furniture at PT Kota Jati Furnindo Jepara.